PENGARUH PASAR MODAL NEGARA G-3 TERHADAP PASAR MODAL ASEAN-5 - Budi Setiawan; Muhammad Hidayat (Jurnal Ilmiah Ekonomi Global Masa Kini)
The stock market has captured the attention of many practitioners and scholars in the past decade. It has become one of the most vital aspects of a modern market economy. The stock market provides companies with access to capital and gives opportunity for investors to have a slice of company ownership. The present paper investigates the impact of G-3 stock markets (US, Japan and Europe) to ASEAN-5 stock markets (Indonesia, Malaysia, Philippines, Thailand and Singapore). The data coverage is composed of daily closing stock index at G-3 stock markets and ASEAN-5 stock markets over the period from January 4, 2000 to December 31, 2014. The historical stock market data were analyzed by using Structured Equation Model (SEM). The empirical results suggest that the G-3 stock markets have a positive and significant impact on ASEAN-5 stock markets. For further, the researcher could add other Asia stock markets such as Nikkei225 Index (Japan), Hang Seng Index (Hong Kong), Kospi Index (South Korea), and BSE Index (India).Keywords: G-3 Stock Markets, ASEAN-5 Stock Markets, Structured Equation Model, Stock Market Diversification; Contagious Effect.